PENGARUH LAJU ALIR INJEKSI GAS EMISI PADA FOTOBIOREAKTOR TERHADAP PENYERAPAN CO 2 OLEH CHLORELLA SP - Santoso, Arif Dwi; Darmawan, Rahmania Admirasari; Susanto, Joko Prayitno (Jurnal Teknologi Lingkungan, 2011)
Carbon dioxide (CO2 )gases that dominated by anthropogenic activities causevarious negative impacts on the environment and surroundings due to increasing itsconcentrations in the atmosphere. There are some techniques to mitigate againstthe increase of CO2 which one is the utilization of phytoplankton cultured in a photobioreactor (FBR) as an natural absorber. In this study, the influence of input gas CO2flowrate on Chlorella sp at multiple tubular air lift photobioractor (FBR) was measuredin milk factory field. The CO2 flowrate continuesly was controled by 2 l/min and 1.5 l/mduring experiment. Result showed that Chlorella sp. have a good adapted ability of CO210-15% vol industrial emition. The experiment result stated that reactor capability atFBR-1 was lower than FBR-2. The reactor capability at FBR-1 and FBR 2 were 0,78 ±0,25 and 0,92 ± 0,36 g/l. media/day.